ANALISIS KEPUASAAN KERJA KARYAWAN DENGAN PENDEKATAN JOB SATISFACTION SURVEY DI PT. ANEKA USAHA TANGGAMUS JAYA - Stefanus Rumangkit; Izzi Musaddad; Indra Jaya; Ary Meizari (Jurnal Bisnis Darmajaya, 2021)
The purpose of this study was to determine what factors influence job satisfaction of employees of PT. Aneka Usaha Tanggamus Jaya. Research Methodology: In this study, the researcher used this type of quantitative research. Quantitative is data in the form of numbers, or quantitative data that is scored (scoring). Data is a source or material that will be used in a study. Data sources consist of primary data Primary Data. The sample in this study were employees of PT. Various Usaha Tanggamus Jaya Lampung, totaling 33 employees. Data analysis using Importance Performance Analysis (IPA)  The results of the importan performance analysis (IPA) show the interpretation of the Cartesian diagram, namely in quadrant A there are 9 attributes that are still not satisfactory and become the main priority to be addressed first by PT. Various Enterprises Tanggamus Jaya. In quadrant B there are 7 attributes that must be maintained by PT. Various Enterprises Tanggamus Jaya. In quadrant C there are 11 attributes that are considered less important or have low priority by employees of PT. Various Enterprises Tanggamus Jaya. In quadrant D there are 9 attributes that are considered not too important by employees.  Research like this related to job satisfaction needs to be done in every industrial sector. This is because, each industry has different antecedents or shapers of job satisfaction. This research is useful for the body of knowledge of human resource management science, especially in the science of employee job satisfaction Keywords — Job Satisfaction, Human Resources Management, Importance Performance Analysis